Physiologic indices of patients before, during and after visit in coronary care unit at Imam Khomeini hospital in Ardebil - Kamrani, Farhad; Seyedjavadi, Mehry; Abedsaeedi, Zhila; Ezzati, zhaleh; Alavimajd, Hamid; Hosseinian, Edalat (Advances in Nursing & Midwifery, 2011)
Physiologic indices of patients before, during and after visit in coronary care unit at Imam Khomeini hospital in Ardebil Kamrani, F.1* (MSN); Seyedjavadi, M.2 (MSN); Abedsaeedi, Zh.3 (PhD); Ezzati, Zh.4 (MSN); Alavimajd, H.5 (PhD); Hosseinian, A.6 (MD) 1. Lecturer, Dept. of Medical-Surgical Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 2. Alumnus, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Science, Tehran, Iran 3. Assistant Professor, Dept. of Medical-Surgical Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Science, Tehran, Iran. 4. Lecture, Dept. of Medical-Surgical Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 5. Associate Professor, Dept. of Biostatistics, Faculty of Paramedical, Shahid Beheshti University of Medical Sciences, Tehran, Iran. 6. Cardiologist, Faculty of Medicine, Ardebil University of Medical Sciences, Ardebil, Iran. Abstract Background and aim Visit is an essential issue in hospitals and of patients’ basic needs in coronary care units (CCUs). However, there is no evidence regarding its physiologic effects on them. The aim of this was to determine the physiologic indexes of patients before, during and after visit at CCU of Imam Khomeini Hospital in Ardebil. Materials and methods In this descriptive study, 50 patients with acute myocardial infarction were selected through convenience sampling method. A questionnaire and a cardiac monitoring device were used for data collection. Content method and calibration the device were used for validity and reliability of the tools respectively. ANOVA with repeated measurements was used for data analysis. Findings %72 of patients was male and %28 was female. Their mean age was 59.8. Significant differences were found between systolic, diastolic and mean arterial pressures; heart as well as respiratory rates; temperature; and oxygen saturation before, during and after the visits. Accordingly, the indexes increased significantly by the start of visits and turned back to the previous state after them with no significant difference in before-after amounts. Conclusion It seems that the physiologic indices of patients change in normal range during visits and return to their primary state after 30 minutes from the end of visits with no clinical importance. Keywords: Visit, Coronary Care Unit (CCU), Physiologic indexes. *Corresponding Author: Lecturer, Dept. of Medical-Surgical Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: comruni1338@yahoo.com